The cancer stem cell antigens CD133, BCRP1/ABCG2 and CD117/c-KIT are not associated with prognosis in resected early-stage non-small cell lung cancer - Herpel, Esther; Jensen, Katrin; Muley, Thomas; Warth, Arne; Schnabel, Philipp Albert; Meister, Michael; Herth, Felix; Dienemann, Hendrik; Thomas, Michael; Gottschling, Sandra (Anticancer research, 2011)
Background: In various tumor entities, expression of cancer stem cell (CSC) antigens has been proven to be prognostically unfavorable. However, for lung cancer, the data are scant and conflicting. Patients and Methods: The CSC antigens CD117/c-KIT, CD133 and breast cancer resistance protein-1 (BCRP1/ABCG2) were immunohistochemically analyzed in tissues from a total of 133 completely resected stage I/II non-small cell lung cancer (NSCLC) patients with a median follow-up time of 53.8 months. Their expression was related to clinicopathological characteristics, angiogenic features and prognosis. Results: Cox proportional hazards regression analysis revealed no association between CSC antigens, disease-free survival or overall survival (OS). However, in the subgroup of patients with relapse and tumors >3 cm, there was a trend towards worse OS upon expression of CD117 (hazard ratio=2.6, 95%, confidence interval=0.8-8.3, p=0.080). Except for CD133, which was overrepresented in T1 tumors (p=0.001), the CSC antigens were not linked to clinico-pathological characteristics or angiogenic features. Conclusion: In resected early-stage NSCLC, CSC antigens show no association with prognosis. However, in patients with relapse and tumors >3 cm, expression of CD117 might predict worse OS.
Gesehen am 06.10.2022